A comprehensive study of the link between star-formation history and X-ray source populations in the SMC - Antoniou, Vallia; Zezas, Andreas; Hatzidimitriou, Despina (2009)
Using Chandra, XMM-Newton and optical photometric catalogs we study the young X-ray binary (XRB) populations of the Small Magellanic Cloud (SMC). We find that the Be/X-ray binaries (Be-XRBs) are observed in regions with star-formation (SF) rate bursts ~30-70 Myr ago, which coincides with the age of maximum Be-star formation, while regions with strong but more recent SF (e.g., the Wing) are deficient in Be-XRBs. Using the 2dF spectrograph of the Anglo-Australian Telescope (AAT) we have obtained optical spectra of 20 High-Mass X-ray Binaries (HMXBs) in the SMC. All of these sources were proved to be Be-XRBs. Similar spectral-type distributions of Be-XRBs and Be field stars in the SMC have been found. On the other hand, the Be-XRBs in the Galaxy follow a different distribution than the isolated Be stars in the Galaxy, in agreement with previous studies.
Keywords: Be; galaxies: individual (SMC); Magellanic Clouds; stars: emission-line; stars: formation; X-rays: binaries